MODEL INSTRUMEN PENILAIAN SEBAGAI ALAT EVALUASI BAGI PENGELOLA DAYA TARIK WISATA PENDIDIKAN ALAM - Nova Eviana; Lenny Yusrini (Panorama Nusantara, 2016)
The purpose of this study is to develop the valid and reliable instrument in assessing the nature-education-based tourist attraction.This instrument is expected as a means of monitoring and evaluating for managers of tourist attraction in the context of meeting the goals of nature education. In the early stages, researchers conducted a theoretical validation involving some tourism experts. Analysis of the data used in this early stage is the Product Moment correlation. Of the 50 items on the instrument, only 43 items were declared valid. Furthermore, the empirical validation through the survey method to visitors of 3 nature-education based tourist attractions were conducted, involving 300 students of elementary school age, by using accidental sampling technique. Determination of the number of respondents follows Gable’s theory. Test of the construct validity of the instrument used Principal Component Analysis (PCA) with varimax rotation. The analysis showed there were 40 valid items, based on the loading factor. The result was further confirmed by a confirmatory method (Confirmatory Factor Analysis) to test the goodness of fit of the model, using the Brown’s criteria of RMSEA, SRMR, CFI, TLI values, and factor loadings as well. While the reliability of the instrument was calculated using Cronbach alpha coefficient ​​with a cut-off value 0.60. The results of validity and reliability test is an instrument with 40 items.